Changing periphery of the Baltic cities: Lithuanian case - Cirtautas, Matas (Journal of Architecture and Urbanism, 2015)
Urban sprawl is one of the dominant types of urban development in the world. Although outer growth started from the outset of cities, urban researchers, planners and policy makers are highly concerned about its current extent. Recent development of the Baltic cities and especially trends of their suburban growth have been analysed only partly, because of the relative novelty of the phenomenon and well-established dominance of western cities in the field. This paper attempts to fill this gap and presents a research on conditions and consequences of extensive development of Lithuanian cities. Evidences from the recent growth of the Baltic cities show that decline and sprawl take place simultaneously in major urban regions with possible long-term consequences on their spatial structure. Therefore, this article advocates a need to revise urban policy in the Baltic countries and promote coordinated development of urban and suburban areas in the context of prevailing negative demographic trends and limited capacity of central and local governments to interfere in urban development processes.